SIKAP PETANI TERHADAP POLA DAN SIFAT KOMUNIKASI DALAM PENYULUHAN PERTANIAN DI KELURAHAN MUGIREJO KECAMATAN SUNGAI PINANG KOTA SAMARINDA (Farmer's Attitude towards the Patterns and Forms Communications in Agricultural Extension in Mugirejo Urban Village, Sungai Pinang Subcity, Samarinda City) - RIZQY MUFADHILAH; RITA MARIATI; NIKE WIDURI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2021)
The purposes of this research were to determine the patterns and forms of communications and attitude of farmers in agricultural extension. This research was conducted from May to July 2019 in Mugirejo Urban Village, Sungai Pinang Subcity, Samarinda City. The number of respondents was 34 farmers. The data analysis method used is descriptive analysis. The results of research showed that the pattern of communication between agricultural extension worker and farmers in agricultural extension in Mugirejo is in the moderate category with a score of 37.96 in terms of four indicators, namely intrapersonal, interpersonal, group, and mass indicators. The form of communication is included in the good category in terms of four indicators, namely the communication forms of face-to-face, media, verbal and non-verbal. The attitude of farmers in agricultural extension to the patterns and forms of communication is categorized as sufficient in terms of three indicators, namely conative, cognitive, and affective.